MEMBANGUN MANAJEMEN KERJA DALAM PERKANTORAN UNTUK MENCAPAI TUJUAN ORGANISASI BERBASIS OFFICE AUTOMATION SYSTEM - Akmaludin Akmaludin (Cakrawala - Jurnal Humaniora, 2012)
The importance value of information within an organization especially in the office, giving to theorganization claims to be able to process with help of technology that is automatic. The conceptshould be applied to organize the information is to use office automation systems that can supportthe receipt, processing, distribution, and storage of all forms of information. Office automationcan run well, certainly with the support of computer technology capable of processing data andinformation very large. This is certainly supported by reliable human resources, and support bothhardware and software. Office automation is a system that strongly supports the distribution ofinformation, both required by the organization's especialy to internal organization and externalorganization, in essence, an office automation system is a system capable of supporting andmanaging all of office activities to be carried out easily and more quickly to information needsgradually, especially within organizations such as offices. Many companies are able to thrive intheir organizations because management activities are supported by office automation system. Infact, its use in organization of office automation systems have strengths and weaknesses, but muchmore beneficial than not using it.Keywords: Information, office automation system, management, organization